Adsorbable and Antimicrobial Amphiphilic Block Copolymers with Enhanced Biocompatibility - Wolf‐Brandstetter, Cornelia; Methling, Rafael; Kuckling, Dirk (Macromolecular Materials and Engineering)
Abstract To minimize or avoid the use of antibiotics, antimicrobial polymers have emerged as a promising option to fight biomaterial‐associated infections, e.g., on titanium‐based implants. However, the challenge is to develop active polymers that exhibit an antimicrobial effect and are compatible with human cells. Different studies aiming for biocidal polymers active in soluble mode, focused on the ratio of cationic to hydrophobic groups, while only marginal knowledge is available for immobilized components. Here a strong hydrophilic electrolyte 4‐vinylbenzyltrimethylammonium chloride (TMA) is chosen as the cationic component. The block composition of the polycationic segment is modified with styrene (Sty) regarding the amphiphilic balance. To adsorb such polymers onto titanium surfaces they are equipped with a polyphosphonic acid anchor block by sequential reversible‐addition‐fragmentation chain‐transfer polymerization (RAFT) polymerization. The polymer composition affected the wetting behavior of adsorbed coatings with water contact angles ranging from 17° to 72°, while zetapotential measurements confirmed high extent of positive charges for all adsorbed polymer coatings. The fundamentally modified block composition resulted in significantly improved cytocompatibility. Antimicrobial efficacy in early bacterial adhesion is still retained from slightly antiadhesive coatings to combined antiadhesive/biocidal activity depending on Sty/TMA ratio in random polymers while a block copolymer revealed lowest antimicrobial effect.
Keywords: antiadhesive surfaces; antimicrobial polymers; grafting to; polymerbrushes

Dynamics of Electron–Hole Coulomb Attractive Energy and Dipole Moment of Hot Excitons in Donor–Acceptor Polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Electrochemical Removal of HF from Carbonate-based LiPF6-containing Li-ion Battery Electrolytes - Ge, Xiaokun; Huck, Marten; Kuhlmann, Andreas; Tiemann, Michael; Weinberger, Christian; Xu, Xiaodan; Zhao, Zhenyu; Steinrueck, Hans-Georg (Journal of The Electrochemical Society)
Due to the hydrolytic instability of LiPF6 in carbonate-based solvents, HF is a typical impurity in Li-ion battery electrolytes. HF significantly influences the performance of Li-ion batteries, for example by impacting the formation of the solid electrolyte interphase at the anode and by affecting transition metal dissolution at the cathode. Additionally, HF complicates studying fundamental interfacial electrochemistry of Li-ion battery electrolytes, such as direct anion reduction, because it is electrocatalytically relatively unstable, resulting in LiF passivation layers. Methods to selectively remove ppm levels of HF from LiPF6-containing carbonate-based electrolytes are limited. We introduce and benchmark a simple yet efficient electrochemical in situ method to selectively remove ppm amounts of HF from LiPF6-containing carbonate-based electrolytes. The basic idea is the application of a suitable potential to a high surface-area metallic electrode upon which only HF reacts (electrocatalytically) while all other electrolyte components are unaffected under the respective conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Cold denaturation of DNA origami nanostructures - Dornbusch, Daniel; Hanke, Marcel; Tomm, Emilia; Kielar, Charlotte; Grundmeier, Guido; Keller, Adrian; Fahmy, Karim (Chemical Communications)
The coupling of structural transitions to heat capacity changes leads to destabilization of macromolecules at both, elevated and lowered temperatures. DNA origami not only exhibit this property but also provide...
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Heterogeneous Structural Evolution of In–Zn–O Thin Films during Annealing - Moffitt, Stephanie L.; Cao, Chuntian; Van Hest, Maikel F. A. M.; Schelhas, Laura T.; Steinrück, Hans-Georg; Toney, Michael F. (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Measurement, Modelling, and Appli cation of Lubricant Properties at Extreme Pressures - Wingertszahn, Patrick; Schmitt, Sebastian; Thielen, Stefan; Oehler, Manuel; Magyar, Balázs; Koch, Oliver; Hasse, Hans; Stephan, Simon (Tribologie und Schmierungstechnik)
Lubricants play a central role in many technical applications, e.g. in bearings and gears as well as in machining processes. In such applications, lubricants are exposed to extreme conditions in the contact area. In lubrication gaps, the pressure can reach values up to 5 GPa. The thermophysical properties of lubricants, and in particular the viscosity, at such extreme conditions have an important influence on the friction and wear behavior of a tribosystem. Accordingly, reliable lubricant property models are a prerequisite for accurate tribological simulations, e.g. elastohydrodynamic lubrication (EHL) simulations. Presently, the vast majority of experimental thermophysical property data are only available up to 1 GPa. Thus, reliable and robust models with strong extrapolation capabilities to higher pressure are required. In this work, viscosity measurements of squalane in a temperature range be tween 20 °C and 100 °C and pressures up to 1 GPa were carried out. Based on that data, a physical model for the viscosity was developed. The model is built by combining a molecular-based equation of state with the so-called entropy scaling approach. Finally, we demonstrate how this fluid property model can be favorably integrated in an EHL simulation by an application programming interface (API). The novel hybrid modeling approach is promising for future applications.
Keywords: Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanical Engineering; Mechanics of Materials

Understanding the Redox Mechanism of Sulfurized Poly(acrylonitrile) as Highly Rate and Cycle Stable Cathode Material for Sodium-Sulfur Batteries - Kappler, Julian; Tonbul, Güldeniz; Schoch, Roland; Murugan, Saravanakumar; Nowakowski, Michał; Lange, Pia Lena; Klostermann, Sina Vanessa; Bauer, Matthias; Schleid, Thomas; Kästner, Johannes; Buchmeiser, Michael Rudolf (Journal of The Electrochemical Society)
Room temperature sodium-sulfur (RT Na-S) batteries are considered potential candidates for stationary power storage applications due to their low cost, broad active material availability and low toxicity. Challenges, such as high volume expansion of the S-cathode upon discharge, low electronic conductivity of S as active material and herewith limited rate capability as well as the shuttling of polysulfides (PSs) as intermediates often impede the cycle stability and practical application of Na-S batteries. Sulfurized poly(acrylonitrile) (SPAN) inherently inhibits the shuttling of PSs and shows compatibility with carbonate-based electrolytes, however, its exact redox mechanism remained unclear to date. Herein, we implement a commercially available and simple electrolyte into the Na-SPAN cell chemistry and demonstrate its high rate and cycle stability. Through the application of in situ techniques utilizing electronic impedance spectroscopy (EIS) and X-ray absorption spectroscopy (XAS) at different depths of charge and discharge, an insight into SPAN’s redox chemistry is obtained.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Relationship between laser-generated micro- and nanostructures and the long-term stability of bonded epoxy-aluminum joints - Freund, Jonathan; Löbbecke, Miriam; Delp, Alexander; Walther, Frank; Wu, Shuang; Tröster, Thomas; Haubrich, Jan (The Journal of Adhesion)
To improve the mechanical performance and to address current shortcomings of adhesive bonds such as bond degradation due to aging, a pulsed laser surface pretreatment of the metal surfaces of aluminum AW 6082-T6 joints with epoxy adhesive E320 is investigated. The surface treatment of the specimens resulted in increased single-lap shear (SLS) strengths before and after hydrothermal aging in 80°C hot water compared to nonpretreated reference specimens. In order to reveal the correlations of laser parameters, resulting surface morphologies and the SLS strength, differently laser pretreated surfaces were characterized at the micro- and nanoscale using optical and scanning electron microscopies. The surface enlargement was quantified with a digital image analysis of cross-sections prepared from the joint interfaces. An analysis of variances (ANOVA) of the SLS results indicated that the laser parameters power and pulse frequency were most critical for obtaining high SLS strengths. Pretreated joint surfaces with a high micro- and nano-surface enlargement and deep solidification structures provide high SLS strengths of up to 50 MPa and almost negligible aging losses of merely 4%. Undercut structures on the pretreated surfaces were found to be beneficial for the mechanical and aging properties when only limited micro- and nanostructuring was applied.
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Adhesion properties of the hybrid system made of laser-structured aluminium EN AW 6082 and CFRP by co-bonding-pressing process - Wu, Shuang; Delp, Alexander; Freund, Jonathan; Walther, Frank; Haubrich, Jan; Löbbecke, Miriam; Tröster, Thomas (The Journal of Adhesion)
A parameter investigation for manufacturing a hybrid system through the prepreg pressing process was carried out within the scope of this work to achieve optimal adhesion properties. The hybrid specimen comprises an aluminium sheet of alloy EN AW 6082 in T6 condition and a thermoset Carbon Fibre Reinforced Plastics prepreg. The prepreg pressing process allows the curing reaction of epoxy resin and the joining process to occur simultaneously to avoid an additional bonding process step. The surface of the aluminium sheet was pretreated in advance using a pulsed Nd:YAG laser to enhance the bonding properties. In the first step, the shear edge tests investigated the adhesion properties achieved with different consolidation (temperature, time and pressure) and laser parameters. Then, 3-point bending tests were carried out to investigate the influence of the consolidation parameters on the mechanical properties of the Carbon Fibre Reinforced Plastics-laminate. In this way, the optimal parameter sets for manufacturing hybrid structures were determined.
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Conformal Pressure and Fast-Charging Li-Ion Batteries - Cao, Chuntian; Steinrück, Hans-Georg; Paul, Partha P; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew; Kasse, Robert M; Thampy, Vivek; Yusuf, Maha; Nelson Weker, Johanna; Shyam, Badri; Subbaraman, Ram; et al. (Journal of The Electrochemical Society)
Abstract Batteries capable of extreme fast-charging (XFC) are a necessity for the deployment of electric vehicles. Material properties of electrodes and electrolytes along with cell parameters such as stack pressure and temperature have coupled, synergistic, and sometimes deleterious effects on fast-charging performance. We develop a new experimental testbed that allows precise and conformal application of electrode stack pressure. We focus on cell capacity degradation using single-layer pouch cells with graphite anodes, LiNi0.5Mn0.3Co0.2O2 (NMC532) cathodes, and carbonate-based electrolyte. In the tested range (10 – 125 psi), cells cycled at higher pressure show higher capacity and less capacity fading. Additionally, Li plating decreases with increasing pressure as observed with scanning electron microscopy (SEM) and optical imaging. While the loss of Li inventory from Li plating is the largest contributor to capacity fade, electrochemical and SEM examination of the NMC cathodes after XFC experiments show increased secondary particle damage at lower pressure. We infer that the better performance at higher pressure is due to more homogenous reactions of active materials across the electrode and less polarization through the electrode thickness. Our study emphasizes the importance of electrode stack pressure in XFC batteries and highlights its subtle role in cell conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Influence of hydrogel coatings on corrosion and fatigue of iron in simulated body fluid - Huang, Jingyuan; Voigt, Markus; Wackenrohr, Steffen; Ebbert, Christoph; Keller, Adrian; Maier, Hans Jürgen; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Formation of insoluble silver-phases in an iron-manganese matrix for bioresorbable implants using varying laser beam melting strategies - Krüger, Jan Tobias; Hoyer, Kay-Peter; Hengsbach, Florian; Schaper, Mirko (Journal of Materials Research and Technology)
Keywords: Metals and Alloys; Surfaces; Coatings and Films; Biomaterials; Ceramics and Composites

Effect of Surface Hydrophobicity on the Adsorption of a Pilus-Derived Adhesin-like Peptide - Yang, Yu; Huang, Jingyuan; Dornbusch, Daniel; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian; Cheung, David L. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Combined in-situ attenuated total reflection-Fourier transform infrared spectroscopy and single molecule force studies of poly(acrylic acid) at electrolyte/oxide interfaces at acidic pH - Neßlinger, Vanessa; Orive, Alejandro G.; Meinderink, Dennis; Grundmeier, Guido (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Do Lead Halide Hybrid Perovskites Have Hydrogen Bonds? - Ibaceta-Jaña, Josefa; Chugh, Manjusha; Novikov, Alexander S.; Mirhosseini, Hossein; Kühne, Thomas; Szyszka, Bernd; Wagner, Markus R.; Muydinov, Ruslan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Nano-FTIR and chemical force analysis of electrografted aryldiazonium salts on ODT-microcontact printed Au-surfaces - Su, Jiangling; González Orive, Alejandro; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; de los Arcos, T.; Kollmann, S.; Carlet, M. (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Testing, modelling, and parameter identification for adhesively bonded joints under the influence of temperature - Schmelzle, Lars; Striewe, Marius; Mergheim, Julia; Meschut, Gerson; Possart, Gunnar; Teutenberg, Dominik; Hein, David; Steinmann, Paul (Journal of Adhesion Science and Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas D.; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Mn(ii) sub-nanometric site stabilization in noble, N-doped carbonaceous materials for electrochemical CO2 reduction - Kossmann, Janina; Sánchez-Manjavacas, Maria Luz Ortiz; Brandt, Jessica; Heil, Tobias; Lopez Salas, Nieves; Albero, Josep (Chemical Communications)
The reported N-doped noble carbonaceous support provides strong stabilization of Mn( ii ) sub-nanometric active sites as well as a convenient coordination environment to produce CO, HCOOH and CH 3 COOH from electrochemical CO 2 reduction.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis